Secondary forest dynamics in the Amazon floodplain in Peru - Jong, W. de (2001)
Studies in secondary forest in Latin America have largely been confined to terra firme lands. This paper reports on a study of dynamics of secondary forest and its interactions with land use for agriculture and utilization of primary forest in the floodplains of the Uyacali and Amazon rivers in Peru. This environment is marked by more fertile soils than generally found on terra firme lands. Floodplains soils may flood yearly or once every several years. Farmers grow combinations of crops on different agricultural sites, and under annual production and multi-annual regimes. Secondary forest plays an important role in this environment. The main trends in the process of formation of secondary forest have been analysed through a survey among 218 farmers, collecting data on land use, primary and secondary forest management, and other economic activities. The results show that processes of secondary forest formation are influenced by advancing market access, changes in the dominant land type as a result of river floods, and population pressure when villages become older. As villages age farmer's holding tend to become smaller. While this happens private primary forest reserves are replaced by secondary forest, but total forest cover does not decline. The economic importance of secondary forest increases when these forests age, but improved market access seems to off-set this trend. The concept of frontier expansion, and the related change of the role secondary forest in the landscape, typical for colonization areas, does only partly apply to this environment.